Oscillating edge states in one-dimensional MoS2 nanowires - Hai Xu (Nature Communications, 2016)
Unusual properties arise in transition metal dichalcogenides as dimensionality decreases. Here, the authors introduce a templated growth approach to precisely control the width of MoS2nanowires on a substrate, allowing them to reveal a relationship between size and electronic properties.